THE ROLE OF FOREIGN LANGUAGE PROFESSIONALLY ORIENTED IN FORMATION OF SELF-LEARNING SKILLS IN OF STUDENTS OF THE PEDAGOGICAL UNIVERSITY (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the problem of defining the contribution of foreign language professionally oriented to forming self-directed learning skills of Pedagogical University students.